2006
DOI: 10.1164/rccm.200509-1442oc
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nocturnal Arrhythmias with Sleep-disordered Breathing

Abstract: Rationale: Sleep-disordered breathing recurrent intermittent hypoxia and sympathetic nervous system activity surges provide the milieu for cardiac arrhythmia development. Objective: We postulate that the prevalence of nocturnal cardiac arrhythmias is higher among subjects with than without sleepdisordered breathing. Methods: The prevalence of arrhythmias was compared in two samples of participants from the Sleep Heart Health Study frequencymatched on age, sex, race/ethnicity, and body mass index: (1 ) 228 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
629
8
65

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,101 publications
(727 citation statements)
references
References 33 publications
25
629
8
65
Order By: Relevance
“…15 Occurrence of nocturnal arrhythmias in adults with obstructive sleep apnea is well documented. 16 Hence, the sudden development of bradyarrhythmia (see Figure 2) and the pattern of its development is consistent with transient increase in vagal tone.…”
Section: Discussionsupporting
confidence: 55%
“…15 Occurrence of nocturnal arrhythmias in adults with obstructive sleep apnea is well documented. 16 Hence, the sudden development of bradyarrhythmia (see Figure 2) and the pattern of its development is consistent with transient increase in vagal tone.…”
Section: Discussionsupporting
confidence: 55%
“…But only about 20% of OSA is diagnosed, and even a smaller percentage is effectively treated [27][28][29][30]. OSA is a well-known independent risk factor for a variety of diseases related to cardiovascular disease, including hypertension, diabetes, cardiac arrhythmia, stroke, and coronary heart disease [5,8,9,14,31]. For these reasons, increasing the understanding of physiologic interactions among sleeprelated breathing parameters and the cardiovascular system is of substantial importance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the link between obstructive apnoic events and conduction disturbances in adults remains controversial, bradyarrhythmic events are more common in subjects with obstructive sleep apnea than in healthy one. In the Sleep Heart Health Study even if statistically not significative the prevalence of conduction delay arrhythmias was higher in patients with SDB than in that one without [16] . Electrophysiological studies showed normal or pseudonormal parameters of sinus node and atrioventricular conduction in patients with OSA and ventricular asystole [17] .…”
Section: Focus On Bradyarrhythmiasmentioning
confidence: 78%